2018
DOI: 10.1016/j.jid.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Integrative Analysis of RNA Sequencing and MicroRNA Expression Data Reveals Key Biologic Wound Healing Pathways in Keloid-Prone Individuals

Abstract: Kö nig B, Landthaler M, et al. Tattoo pigments are cleaved by laser light-the chemical analysis in vitro provide evidence for hazardous compounds. Photochem Photobiol 2004;80: 185e90. Wilmer JL, Kligerman AD, Erexson GL. Sister chromatid exchange induction and cell cycle inhibition by aniline and its metabolites in human fibroblasts. Environ Mutagen 1981;3: 627e38. This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 10 publications
0
44
0
1
Order By: Relevance
“…While a few gene expression studies have been performed, the majority focused on specific genes or limited microarray studies (25)(26)(27)(28)(29)(30)(31)(32). Furthermore, these studies did not entirely characterize the inflammatory profile of keloids.…”
Section: Introductionmentioning
confidence: 99%
“…While a few gene expression studies have been performed, the majority focused on specific genes or limited microarray studies (25)(26)(27)(28)(29)(30)(31)(32). Furthermore, these studies did not entirely characterize the inflammatory profile of keloids.…”
Section: Introductionmentioning
confidence: 99%
“…24 circRNAs act as a miRNA molecular sponge to regulate the functions of miRNAs. In addition, in the study by Onoufriadis et al, 25 gene association network analysis was also performed to further classify the differentially expressed genes from the RNA-Seq dataset according to reactome pathway terms and correlated expression values among them. It demonstrated a divergent average expression profile of cytokine signaling genes between keloid-prone and healthy individuals during wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrated a divergent average expression profile of cytokine signaling genes between keloid-prone and healthy individuals during wound healing. 25 In consequence, it is key and feasible to better understand circRNAs and to construct lncRNA-miRNA-mRNA network, to explore the specific pathogenesis of keloid.…”
Section: Discussionmentioning
confidence: 99%
“…Such noncoding small RNA molecules play an important role in processes including biological development, metabolism, differentiation, proliferation, and apoptosis. Previous studies have indicated that abnormal expression of miRNAs can cause disease and even cancer, as certain miRNAs function similarly to tumour suppressor genes [12, 13]. Keloids are a type of solid tumour and, in recent years, researchers have focused on the effect of miRNAs on keloid development.…”
Section: Discussionmentioning
confidence: 99%